A house in the sun modern architecture and solar energy in the Cold War - Barber, Daniel A. ca. 20./21. Jh (Oxford University Press, 2016)
'A House in the Sun' describes a number of experiments in solar house heating in the 1940s and 1950s. It shows how resource limitations were seen as an opportunity for design to attain new relevance for social and cultural transformations